Critical Examination of the Relationship Between Land Taxation and Total Internal Revenue Generated in Kano State, Nigeria - Atinuke Orekan (Ilomata International Journal of Tax and Accounting, 2023)
The study examined the relationship between land tax and total IGR as well as the proportion land taxes constitute in the total IGR for a period of twelve years. Data were collected through a well-structured questionnaire, personal interviews and review of government documents. Questionnaires were administered to the 31 top management staff at the Board of Internal Revenue Services in Kano State. At the Bureau of Land Management in Kano State, questionnaires were also administered to 25 senior cadre officers. Personal interviews were also conducted. Using the Pearson Correlation Coefficient, the result of the study showed that there was a positive relationship between land taxes and total IGR in Kano States and the strength of association was strong i.e., (0.989) in Kano State. By implication, land tax forms a major source of revenue in the two study areas. In view of this, the study concluded that for government to continue to provide the necessary infrastructure and also maintain them through revenue from land tax, government needs to take into consideration a good property statistics and information together with the property owners, tax laws need to be reviewe\d to tackle tax evasion and at the same time, government should be ready to give proper account of revenue realised through land taxation and this should be published accordingly.